Seeing the unseen - enhancing and evaluating undergraduate polarization experiments with interactive Mixed-Reality technology - Schlummer, Paul; Abazi, A.; Borkamp, R.; Lauströer, J.; Schulz-Schaeffer, R.; Schuck, C.; Pernice, Wolfram; Heusler, S.; Laumann, D. (European journal of physics, 2023)
Learning from hands-on experiments requires learners to interpret their concrete interactions with the setup in terms of abstract physical concepts. To facilitate conceptual learning and close the gap between abstract physical models and the haptic interaction with the pertinent experimental setup, we developed an interactive Mixed-Reality learning environment centred around an undergraduate lab experiment dealing with light polarization. The use of Smartglasses (Microsoft HoloLens II) enables real-time visualization of data measured in the setup and ensures a high degree of spatial and temporal contiguity between functional components and model-based representations. A pilot study with N = 73 undergraduate students was conducted in a pre/post design to evaluate the learning environment with respect to learning outcome and learners’ affection towards the experiment. The results show that students’ knowledge had significantly increased after working with the learning environment with a large effect size (t(72) = 8.50, p ≤ 0.001, d = 1.03), and the activities are perceived as interesting and enjoyable. This proves the effectiveness of the environment with regard to learning about polarization and opens the pathway for an extension of our approach to other topics in science education.
Veröffentlicht: 7. September 2023
Gesehen am 17.10.2023